Targeting the medulloblastoma: a molecular-based approach - Luzzi, Sabino; Giotta Lucifero , Alice; Brambilla, Ilaria; Semeria Mantelli, Simona; Mosconi, Mario; Foiadelli, Thomas; Savasta, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
Background: The lack of success of standard therapies for medulloblastoma has highlighted the need to plan a new therapeutic approach. The purpose of this article is to provide an overview of the novel treatment strategies based on the molecular characterization and risk categories of the medulloblastoma, also focusing on up-to-date relevant clinical trials and the challenges in translating tailored approaches into clinical practice. Methods: An online search of the literature was carried out on the PubMed/MEDLINE and ClinicalTrials.gov websites about molecular classification of medulloblastomas, ongoing clinical trials and new treatment strategies. Only articles in the English language and published in the last five years were selected. The research was refined based on the best match and relevance. Results: A total 58 articles and 51 clinical trials were analyzed. Trials were of phase I, II, and I/II in 55%, 33% and 12% of the cases, respectively. Target and adoptive immunotherapies were the treatment strategies for newly diagnosed and recurrent medulloblastoma in 71% and 29% of the cases, respectively. Conclusion: Efforts are focused on the fine-tuning of target therapies and immunotherapies, including agents directed to specific pathways, engineered T-cells and oncoviruses. The blood-brain barrier, chemoresistance, the tumor microenvironment and cancer stem cells are the main translational challenges to be overcome in order to optimize medulloblastoma treatment, reduce the long-term morbidity and increase the overall survival.